Long-term occlusion results with SILK flow diversion in 28 aneurysms: Do recanalizations occur during follow-up?. Issue 3 (June 2015) - Mpotsaris, Anastasios; Skalej, Martin; Beuing, Oliver; Eckert, Bernd; Behme, Daniel; Weber, Werner
Background and purpose: The purpose of this article is to report on the long-term success rates of Silk flow-diverter (FD) treatment in a multicenter prospective study for the treatment of complex aneurysms. Methods: Between May 2008 and January 2011, all consecutive patients featuring complex intracranial aneurysms eligible for FD treatment with the Silk in three neurovascular centers were included. Clinical and imaging data were assessed during hospitalization and follow-up. Results: Five patients were initially asymptomatic, 20 patients showed various neurological symptoms. Twenty-eight FDs were implanted in 25 patients treating 28 aneurysms. The immediate procedure-related morbidity was 8% (two of 25), mortality 0%. One procedure-related death was observed during follow-up (in-stent thrombosis). Compared to the immediate result nearly two of three aneurysms improved during follow-up; all angiographically confirmed inflow changes took place within six months after treatment. Final anatomic outcome in 24 aneurysms of 22 patients comprised 14 (59%) with complete occlusion, seven (29%) with a neck remnant, two (8%) with residual filling <50%, none with residual filling >50% and one (4%) unchanged in comparison to its pretreatment status. Postinterventional recanalizations were seen in three of 13 (23%) aneurysms treated with FD alone; none were observed in 15 aneurysms treated with adjunctive coiling. Conclusion: Anatomic presentation and location are key for successful FD treatment. The rate of successful occlusion increases during follow-up. Postinterventional monitoring for at least six months is paramount, as anatomic outcome is not reliably predictable and recanalizations may occur in initially completely occluded aneurysms.